GE_GERICHTE P/518/2020 vom 30. Juni 2022 - GE Cour de justice (2022)
CLASSEMENT DE LA PROCÉDURE;IMPUTATION;FRAIS DE LA PROCÉDURE;INDEMNITÉ(EN GÉNÉRAL);FAUTE | CPP.319; CPP.433; CPP.430; CPP.426.al2; CP.158; CP.138